You Will Meet a Tall, Dark Stranger Executive Coaching Challenges - Kets de Vries, Manfred F.R (INSEAD Business Press, 2016)
Kets de Vries profiles a range of toxic executives the narcissist, psychopath, cold fish, obsessive-compulsive, and many more, offering coaches examples of interventions that have worked and those that haven't, to help coaches deal with difficult people and become more effective.